2017
DOI: 10.14701/ahbps.2017.21.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic total pancreatectomy for multiple metastasis of renal cell carcinoma of the pancreas: a case report and literature review

Abstract: Advances in surgical techniques and laparoscopic instruments have resulted in the development of laparoscopic pancreatic surgery. Total pancreaticoduodenectomy is performed for treating benign and borderline pancreatic disease involving the whole pancreas. Here, we report a case of metastatic renal cell carcinoma in the pancreas, treated by laparoscopic pylorus-preserving total pancreaticoduodenectomy. A 59-year-old woman was diagnosed with metastatic renal cell carcinoma. Multiple metastatic lesions were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In summary, this analysis showed that the factor "time of occurrence of metastases" had no influence on OS both when comparing synchronous with metachronous metastases and within the group of metachronous isPM. Comparable results were reported in single institution (177,184) and multicentre reports (182), as well as in two literature reviews (142,194) and in a review of total pancreatectomies in isPM patients (229), which registered no dependence of the results on the interval after a nephrectomy.…”
Section: Synchronous and Metachronous Metastases In Ispmsupporting
confidence: 71%
“…In summary, this analysis showed that the factor "time of occurrence of metastases" had no influence on OS both when comparing synchronous with metachronous metastases and within the group of metachronous isPM. Comparable results were reported in single institution (177,184) and multicentre reports (182), as well as in two literature reviews (142,194) and in a review of total pancreatectomies in isPM patients (229), which registered no dependence of the results on the interval after a nephrectomy.…”
Section: Synchronous and Metachronous Metastases In Ispmsupporting
confidence: 71%
“…The head of the pancreas (41.8%) is the most common site of pancreatic metastases, followed by the body and tail of the pancreas (34.9%) and the ampulla area (8.9%) [6]. More than half of patients with pancreatic metastases are usually asymptomatic, and most metastases are found during a follow-up treatment of the primary tumour [7]. Patients that are symptomatic often have nonspeci c complaints, such as abdominal pain, anaemia, weight loss, vomiting, jaundice, or bleeding in the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…This example illustrates that by closely monitoring blood glucose and providing extra trypsin after total pancreatectomy, the patient could have a better quality of life. In addition to the widely used prognostic factor model from the Memorial Sloan Kettering Cancer Center [ 31 33 ], vascular invasion [ 2 ], presence of symptoms [ 34 ], and tumor size more than 3 cm [ 35 ] may be associated with an increased risk of death. However, the localization and number of metastatic lesions have no effect on the site of metastases [ 34 ], which is in line with our current results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the localization and number of metastatic lesions have no effect on the site of metastases [ 34 ], which is in line with our current results. Although a few researchers believe that lymphadenectomy should be considered for pancreatic metastasis [ 35 ], there is no convincing evidence to indicate that the involvement of lymph nodes in pancreatic metastasis may affect prognosis [ 8 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%